2014
DOI: 10.1097/01.dss.0000452662.69539.57
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Modulated Photodynamic Therapy for the Treatment of Actinic Keratosis on the Extremities

Abstract: Warming the skin during incubation of ALA seems to improve the efficacy of PDT in the treatment of AKs on the extremities and is well tolerated when heat application is controlled within the limits of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…The increased PpIX fluorescence from RG2 tumors in vivo following hypothermia is expected from our in vitro studies but contrary to studies on skin demonstrating an increase PpIX accumulation at 38.5°C versus 29°C [ 33 ]. This may be attributable to the much lower temperature in that study; 29°C being considered outside the range of mild hypothermia and not examined in this work.…”
Section: Discussioncontrasting
confidence: 96%
“…The increased PpIX fluorescence from RG2 tumors in vivo following hypothermia is expected from our in vitro studies but contrary to studies on skin demonstrating an increase PpIX accumulation at 38.5°C versus 29°C [ 33 ]. This may be attributable to the much lower temperature in that study; 29°C being considered outside the range of mild hypothermia and not examined in this work.…”
Section: Discussioncontrasting
confidence: 96%
“…hands, arms, legs, chest) [24] and may represent a reduced barrier to ALA distribution, and in turn increased PpIX production in the face. Second, skin temperature may be lower on extremities than on the face, resulting in lower PpIX generation on the arms and legs [25]. The observed differences in PpIX generation also appear to be patient-specific, with a correlation observed between PpIX concentration in AK lesions and normal locations on a per-patient basis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Willey et al [16] reported the efficacy and tolerability of temperature-modulated PDT for the treatment of AKs on the extremities. The upper and/or lower extremities of 20 subjects were treated with 20% ALA-PDT.…”
Section: Clinical Applicationsmentioning
confidence: 99%